Isotype and antibody specificity of spontaneously formed immunoglobulins in pig fetuses and germ-free piglets: production by CD5- B cells - Cukrowska, B; Sinkora, J; Reháková, Z; Sinkora, M; Splíchal, I; Tucková, L; Avrameas, S; Saalmüller, A; Barot-Ciorbaru, R; Tlaskalová-Hogenová, H (Immunology, 1996)
Pig fetuses, colostrum-deprived newborns and germ-free (GF) piglets, animals in which B-cell development is not influenced by maternal regulatory factors, were employed to study the occurrence and specificity of natural antibodies (NAb). Serum immunoglobulins of all isotypes were found in 44-day-old fetuses (the gestation period in pigs lasts 114 days) and their level, with predominating IgM, was increased during fetal ontogeny. In sera of fetuses at the end of embryonic life as well as of newborns and older GF piglets, antibody activity against autoantigens (thyroglobulin, hormones, ssDNA), phylogenetically conserved proteins (myosin), haptens (trinitrophenyl; TNP) and bacterial components (Escherichia coli O86, tetanic anatoxin) was detected by enzyme-linked immunosorbent assay. The antigen-biding activity of IgM NAb increased after isolation of the serum immunoglobulins on a Staphylococcus Protein A (SPA)-Sepharose column. IgM reactivity similar to that detected in serum was found in supernatants from polyclonally stimulated cultures of spleen of 8- and 12-day-old GF piglets. Pig fetal liver IgM+ B cells, which were able to produce IgM after polyclonal stimulation, did not express the CD5 molecule. Our results indicate that pig preimmune repertoire is comparable to that described in humans and mice, although in contrast to these species pig B-1 cells do not express CD5.
Keywords: Liver; Animals; novorozená zvířata; gnotobiologické modely; plod; CD5 Antigens; játra; Immunoglobulin Isotypes; imunoglobulin M; Animals, Newborn; Fetus; prasata; antigeny CD5; Immunoglobulins; Germ-Free Life; Swine; Immunoglobulin M; B-Lymphocytes; Antibody Specificity; B-lymfocyty; imunoglobulinové izotypy; specificita protilátek; buněčné kultury; zvířata; imunoglobuliny; Cell Culture Techniques